Acute phase response in organic lambs associated with colostrum serum amyloid A, weight gain, and Cryptosporidium and Giardia infections. (December 2018) - Niine, Tarmo; Peetsalu, Kristel; Tummeleht, Lea; Kuks, Ants; Orro, Toomas
Abstract: In neonatal period, lamb's immune system goes through rapid adaptation to the extra-uterine environment. Success of this process can influence the animal's future performance and, thus, the quantitative assessment of it would greatly benefit sheep producers. The current study was conducted to investigate the acute phase response (APR) (measured through serum amyloid A (SAA), haptoglobin (Hp) and albumin (ALB)) in relation to later life growth (measured at 122 days of age), and naturally occurring Cryptosporidium and Giardia infections in neonatal lambs grown in organic farm. Serum ( n = 692) and faecal ( n = 141) samples were collected from 269 lambs in their first 3 weeks of life. The ewes' colostrum ( n = 181) SAA concentrations were positively associated with the lambs' serum SAA and Hp concentrations at 2 to 4 days of age. Hp and ALB concentrations at the second week of age were positively associated with the growth rate at 122 days of age. Lamb serum globulin (GLOB) concentrations and Cryptosporidium -positive faecal samples were negatively associated at the second and third weeks of life. These findings suggest the importance of interactions between the immune system and environmental factors at the second week of the lambs' lives and its association with future performance. Highlights: Colostral serum amyloid A (SAA) was associated with lamb serum SAA and haptoglobin (Hp) at 2 to 4 days of age. Hp and albumin in the second week of life were positively associated with average daily weight gain at 122 days of life. Lambs' serum globulins concentrations and diagnosis of Cryptosporidium -positive faecal samples were negatively associated.